Friendship Club - Carr, Robyn (Toronto, Ontario, Canada Mira, 2024)
"Celebrity cooking show host Marni McGuire has seen it all. She's been married--twice--and widowed and divorced. Now in her midfifties, she's single. Happily so. She just needs to convince her pregnant daughter, Bella, of this fact. And maybe convince herself, too. Especially after Marni's efforts to humor her determined daughter result in a series of disastrous dates that somehow prompt Marni to wonder if maybe the right man for her is still out there after all. Similarly single, Marni's best friend and colleague is confident she's content without a man, but both older women soon find themselves leading by example as the young intern on their show appears caught in a toxic relationship, and Bella reveals her own marriage maybe isn't built to withstand the stresses of the baby on the way. Suddenly, all four women find themselves at a crossroads, each navigating the challenges of dating, marriage, loneliness and love. Thankfully, they have each other to lean on. The realities of modern love are far from easy, but there's no better group to have in your corner than friends who will lift you up, no matter what, and hold fast in the face of any storm." --
Includes an excerpt for What We Find (pages 307-330).
113106
Keywords: Television cooking shows -- Fiction; Celebrity chefs -- Fiction; Celebrities -- Fiction; Divorced people -- Fiction; Dating (Social customs) -- Fiction; Female friendship -- Fiction; Divorced women -- Fiction; Abused women -- Fiction; Romance fiction; Domestic fiction